Supervision in higher education : a research ethics perspective - Wittek, Line (Great debates in higher education., 2025)
A lot of uncertainty exists among professors in higher education about what the role. of supervisor entails. This uncertainty concerns, among other things, what it means to comply with research ethical principles. Wittek brings together new knowledge and information concerning international guidelines for research ethics in relation to reliability, honesty, respect and accountability; empirical studies on supervision that sheds light on research integrity in supervision and guidance; and practical cases and questions taken from real situations in higher education. Chapters focus on what supervisors can do to make the ethical guidelines transparent and ensure that their practice is in accordance with the European Federation of Academies of Sciences and Humanities (ALLEA) principles. The challenges discussed include how is trust established in guidance and supervision, co-authorship and ownership of data and the need for supervisors to be responsive and sensitive to the vulnerability that can characterise younger researchers who are in an early phase of their career. Supervision in Higher Education: A Research Ethics Perspective unpacks what current research ethical principles can mean for the supervision of PhD and MA candidates and provides guidance for less formalised contexts. A must-read for supervisors in higher education across all disciplines and professions.